Distribution and abundance of Aedes mosquito breeding sites at construction site workers’ hostel in Gelang Patah, Johor, Malaysia - Shahril Hamidun,; Farah Ayuni Shafie,; Ahmad Razali Ishak,; Nazri Che Dom, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
In recent decades, the increase of dengue epidemic cases is likely due to the rapid and broad-ranging migration of people and urbanization. Knowing the source is a critical key component for the disease transmission. The main objective of the study was to assess the relationship between the residential area and non-residential area at the construction site workers’ hostel towards the Aedes breeding distribution and abundance from May 2019 to September 2019. Distribution and abundance of Aedes mosquito was determined by using Positive Ovitrap Index (POI) and Mean Eggs per Trap (MET). From 400 ovitraps placed, residential area (Zone A) has the highest number of positive ovitraps with a total of 86 positive ovitraps out of 167 ovitraps that were successfully retrieved with the index of 51.50%. Non-residential area (Zone B) has a total of 60 positive ovitraps out of 152 ovitraps with the index of 39.47%. The number of eggs identified from Zone A was 1656 eggs with MET value of 19.35 while for Zone B, the number of eggs identified was 1025 eggs with MET value of 17.09. The P-value obtained for distribution and abundance was 0.05, which means that there is no significant difference in POI and MET for the two types of land use. The outcome of the distribution and abundance from this study can be used to design appropriate strategies to control the vector population and predict the disease transmission. It should also provide a base-line information that is essential for future studies in different types of land uses and towards better understanding of population dynamics of Aedes mosquito under local conditions.